2017
DOI: 10.1037/apl0000168
|View full text |Cite
|
Sign up to set email alerts
|

The importance of being “me”: The relation between authentic identity expression and transgender employees’ work-related attitudes and experiences.

Abstract: The present research examined the relation between authentic identity expression and transgender employees' work-related attitudes and experiences. Drawing on Kernis' (2003) theoretical conceptualization of authenticity and expanding on current workplace identity management research, we predicted that employees who had taken steps to reduce the discrepancy between their inner gender identities and their outward manifestations of gender would report more positive job attitudes and workplace experiences, in part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
105
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 70 publications
6
105
0
1
Order By: Relevance
“…This relationship was supported across concealable stigmatized identity groups including sexual orientation (Griffith & Hebl, ; Huffman & King, 2008; James, 2010; Ragins et al, ; Sabat et al, ), disability (Roebuck et al, ), pregnancy (Sabat et al, Unpublished), and gender identity (Martinez et al, ). Specifically, disclosure was associated with increased perceptions of coworker support (Griffith & Hebl, ; Huffman, Watrous‐Rodriguez, & King, ; Roebuck et al, ; Weiss, 2003), increased perceptions of supervisor support (Huffman, Watrous‐Rodriguez, & King, ; Weiss, 2003; Sabat et al, unpublished), decreased interpersonal discrimination (Sabat et al, ; Roebuck et al, 2014, Sabat et al, unpublished), and decreased formal discrimination (Martinez et al, ). Another positive outcome of disclosure is that it reduced tensions between employees at work as found in a study of gay and lesbian Taiwanese workers in which reduced work stress mediated the relationship between disclosure and job effectiveness.…”
Section: Disclosure In the Workplace: A Review Of What We Knowmentioning
confidence: 93%
See 2 more Smart Citations
“…This relationship was supported across concealable stigmatized identity groups including sexual orientation (Griffith & Hebl, ; Huffman & King, 2008; James, 2010; Ragins et al, ; Sabat et al, ), disability (Roebuck et al, ), pregnancy (Sabat et al, Unpublished), and gender identity (Martinez et al, ). Specifically, disclosure was associated with increased perceptions of coworker support (Griffith & Hebl, ; Huffman, Watrous‐Rodriguez, & King, ; Roebuck et al, ; Weiss, 2003), increased perceptions of supervisor support (Huffman, Watrous‐Rodriguez, & King, ; Weiss, 2003; Sabat et al, unpublished), decreased interpersonal discrimination (Sabat et al, ; Roebuck et al, 2014, Sabat et al, unpublished), and decreased formal discrimination (Martinez et al, ). Another positive outcome of disclosure is that it reduced tensions between employees at work as found in a study of gay and lesbian Taiwanese workers in which reduced work stress mediated the relationship between disclosure and job effectiveness.…”
Section: Disclosure In the Workplace: A Review Of What We Knowmentioning
confidence: 93%
“…On the other hand, several studies reported negative relationships between disclosure and interpersonal outcomes. Such findings were obtained in samples comprised of individuals with multiple concealable stigmatized identities including sexual orientation (Arena & Jones, ; Ragins et al, ; Swank, Fahs, & Frost, ), religion (Ahmad et al, , April), HIV status (Weiss, 2003), and gender identity (Martinez et al, ). Interestingly, the outcomes associated with disclosure of one's sexual orientation may depend, in part, on the specific identity.…”
Section: Disclosure In the Workplace: A Review Of What We Knowmentioning
confidence: 97%
See 1 more Smart Citation
“…International quantitative and qualitative studies suggested a positive relationship between transitioning and mental health (Cardoso da Silva et al, 2016;Brewster et al, 2014, Callan, 2014, Brewster et al, 2012, Dhejne et al, 2016, Murad et al, 2010, De Cuypere et al, 2006, Lobato et al, 2006, Smith et al, 2005, De Cuypere et al, 2005, Green, 2005, transitioning and life satisfaction (van de Grift et al, 2017;Bockting et al, 2016;Brewster et al, 2014, Brewster et al, 2012, Salvador et al, 2012, Parola et al, 2010, Lobato et al, 2006, De Cuypere et al, 2006, Smith et al, 2005) and transitioning and job satisfaction (Martinez et al, 2017;Brewster et al, 2014;Brewster et al, 2012;Scottish Transgender Alliance and Stonewall Scotland, 2012;Morton, 2008).…”
Section: Introduction: the Trans Curvementioning
confidence: 99%
“…IM is important to consider because of its connection to downstream consequences related to retaining women in STEM occupations. That is, research and theory connect IM choices to job satisfaction, turnover intentions, and physical and mental well‐being (Jones et al ., ; Lyons, Wessel, Ghumman, Ryan & Kim, ; Madera, King, & Hebl, ; Martinez, Sawyer, Thoroughgood, Ruggs, & Smith, ).…”
Section: Introductionmentioning
confidence: 99%